Zaufanie do nauki: perspektywa krytyczno-racjonalistyczna - Adam Chmielewski (Studia Philosophica Wratislaviensia)
In this paper, I discuss whether the critical rationalist philosophy of science can help to contain the current propagation of public distrust of science and to build public trust in science-based technologies. Since critical rationalism views science as demanding bold theories and rigorous testing, it is reasonable to claim that such an attitude should be taken as a compelling argument for the trustworthiness of scientific knowledge. I argue, however, that such a view will not suffice to bolster the public trust in science because, as it became recently obvious, it is precisely this attitude that is nowadays exploited to undermine confidence in science and science-based technologies. For this reason, I claim that providing a more compelling argument on behalf of trust in science will require the critical rationalist philosophy to address institutional, social and political issues involved in knowledge construction, which thus far remained outside the scope of its interests.